1901 Conn. Acts 602 (Spec. Sess.) - (:unkn) unknown (My University, 1901)
§ 20: Granted the county of New Haven the authority to regulate the discharge of firearms within the Borough. Also granted the authority to license, regulate, or prohibit the manufacture, keeping for sale, and use of fireworks, torpedoes, firecrackers, gunpowder, petroleum, dynamite, or other explosive or inflammable substance.
Keywords: DISCHARGE; TRANSFER, MANUFACTURE & STORAGE OF GUNPOWDER